Insights Into Mechanisms of Oriented Division From Studies in 3D Cellular Models - Donà, Federico; Eli, Susanna; Mapelli, Marina (Frontiers in Cell and Developmental Biology, 2022)
In multicellular organisms, epithelial cells are key elements of tissue organization. In developing tissues, cellular proliferation and differentiation are under the tight regulation of morphogenetic programs, that ensure the correct organ formation and functioning. In these processes, mitotic rates and division orientation are crucial in regulating the velocity and the timing of the forming tissue. Division orientation, specified by mitotic spindle placement with respect to epithelial apico-basal polarity, controls not only the partitioning of cellular components but also the positioning of the daughter cells within the tissue, and hence the contacts that daughter cells retain with the surrounding microenvironment. Daughter cells positioning is important to determine signal sensing and fate, and therefore the final function of the developing organ. In this review, we will discuss recent discoveries regarding the mechanistics of planar divisions in mammalian epithelial cells, summarizing technologies and model systems used to study oriented cell divisions in vitro such as three-dimensional cysts of immortalized cells and intestinal organoids. We also highlight how misorientation is corrected in vivo and in vitro, and how it might contribute to the onset of pathological conditions.